Cardio-respiratory indicators and functional state of athletes after COVID-19 - Yulia M. Ivanova; Viktoriya A. Badtieva; Alexander S. Sharykin; Vladimir I. Pavlov; Nataliya V. Trukhacheva (Спортивная медицина: наука и практика)
Purpose of the study: to assess the state of the cardiorespiratory system of athletes after the COVID-19 pandemic.Materials and methods: A total of 1096 athletes (492 women and 604 men) over 15 years of age were examined in 28 sports. A clinical and instrumental assessment of the health of the athletes, a laboratory analysis by the polymerase chain reaction (PCR) method for the genetic material of the virus and the level of IgM and IgG antibodies to the SARS-CoV-2 virus, an assessment of the functional state of the cardiorespiratory system were carried out.Results: None of the athletes included in the study were hospitalized or had symptoms of pneumonia or cardiovascular problems. The period of self-isolation with limited self-training lasted from 2.5 to 3 months. After isolation, a decrease in the aerobic capacity of the athletes was noted. The peak oxygen consumption achieved during this period significantly decreased compared to the period before self-isolation in all types of sports disciplines.Conclusions: Athletes are at high risk of contracting coronavirus infection and require mandatory testing for the infection before being allowed to train and compete. The main consequence of self-isolation is a decrease in the predominantly aerobic performance of athletes, regardless of whether they have had COVID-19.